Extraction Performance of a Fluorous Phosphate for Zr(IV) from HNO3 Solution: Comparison with Tri-n-Butyl Phosphate. Issue 5 (29th July 2019) - Ueda, Yuki; Kikuchi, Kei; Sugita, Tsuyoshi; Motokawa, Ryuhei
ABSTRACT: We compare the extraction performance of new extractant, fluorous phosphate tris(4, 4, 5, 5, 6, 6, 7, 7, 7-nonafluoroheptyl) phosphate (TFP) in the fluorinated diluent perfluorohexane, for Zr(IV) with a conventional organic extractant, tri- n -butyl phosphate (TBP) in n -octane. It is surprising that fluorinating TBP to TFP improved the extraction performance, as normally fluorinating the hydrocarbon substituents on neutral extractants tends to decrease the extraction strength. We examined the origin of the superior extraction performance of TFP by analyzing the equilibrium of the chemical reaction during the extraction. The equilibrium reaction of Zr(IV) with TFP is Z r N O 3 4 a q + 3 T F P f l u   ⇌ Z r N O 3 4 T F P 3 f l u, whereas that with TBP is Z r N O 3 4 a q + 2 T B P o r g   ⇌ Z r N O 3 4 ( T B P ) 2 o r g . Phosphorus-31 nuclear magnetic resonance and infrared spectroscopy measurements of TFP and TBP showed similar electron densities at the phosphorus atom and vibration modes of the P =O group, implying similar coordination to Zr(IV). In addition, the concentrations of all components (Zr(IV), HNO3, and water) in the fluorous and organic phases after solvent extraction were evaluated by inductively coupled plasma-mass spectrometry, ion chromatography, and Karl-Fischer titration. The concentrations of water and HNO3 molecules in the fluorous phase become low during the Zr(NO3 )4 (TFP)3 extraction, indicating that water and HNO3 molecules do not preferentially interact with Zr(NO3 )4 (TFP)3 in contrast to Zr(NO3 )4 (TBP)2 in n -octane We speculate that the excellent performance originated from the stability of Zr(NO3 )4 (TFP)3 in the fluorous phase. Hence, TFP is expected to be used as an alternative extractant to TBP.